Meta-analysis of epilepsy prevalence in West Africa and its relationship with onchocerciasis endemicity and control - (:unkn) unknown (My University, 2020)
Background: A high prevalence and incidence of epilepsy has been reported in onchocerciasis-endemic regionsin Central and East Africa. There is compelling epidemiological evidence suggesting that this high burden iscaused by onchocerciasis-associated epilepsy (OAE).We hypothesized that OAE had also occured inWest Africanonchocerciasis foci.Methods: We searched PubMed, the African Journals Online platform and grey literature for population-basedepilepsy studies inWest African countries. Epilepsy and onchocerciasis prevalence data were extracted. The precontrolonchocerciasis endemicity in the study siteswas estimated from historical data of onchocerciasis controlprogrammes. The prevalence of epilepsy in different sites was analysed, taking into account onchocerciasisendemicity and the duration of control.Results: The pooled prevalence of epilepsy in theWest African study sites was 13.14 per 1000 (95% confidenceinterval 11.28–15.00). Higher pre-control endemicity and a shorter duration of onchocerciasis control were bothassociated with increased epilepsy prevalence (p<0.001). Two studies in Ivory Coast that provided detaileddescriptions of persons with epilepsy in onchocerciasis-endemic settings revealed that most of them hadfeatures of OAE (73.7% and 83.3%, respectively).Conclusions: Our findings suggest that before and during the early years of implementing onchocerciasis controlinWest Africa, high onchocerciasis endemicity resulted in a high prevalence of OAE and that subsequent controlefforts significantly reduced the prevalence of OAE.
Keywords: African Research